Characterization of plasmid pXL100 from Amycolatopsis orientalis HCCB10007 and construction of a shuttle vector. (11th November 2014) - Xu, Li; Li, Yanmei; Zhu, Li; Zhao, Wei; Chen, Daijie; Huang, Weiyi; Yang, Sheng
<x xml:space="preserve">Abstract</x> Many strains of Amycolatopsis, such as Amycolatopsis orientalis, A. balhimycina, and A. mediterranei, are important antibiotic producers. Three indigenous plasmids, pMEA100, pMEA300, and pA387, found in this genus have been sequenced. However, only some vectors based on pA387 have been widely applied in Amycolatopsis research. An indigenous plasmid, pXL100, was isolated from the vancomycin producer A. orientalis HCCB10007. Sequence analysis of pXL100 revealed its total length to be 33, 499 bp and GC content to be 68.9%. A 2830‐bp fragment containing three ORFs has been identified as essential for replication in A. orientalis, but it has no significant similarity to any known replicons. A vector, pLYZW7‐3, was constructed based on the pXL100 replicon and could be transferred into A. mediterranei and A. orientalis by electroporation or conjugation with high frequency. A mutant with a disrupted gene was successfully complemented with the pLYZW7‐3 vector, indicating that the vector is potentially useful in Amycolatopsis research.